(untitled) (Iranian Journal of Kidney Diseases, 2012)
Ibn-Sina (commonly known as Avicenna) is one of the most famous and influential scientists in the history of medicine. The Canon of Medicine, which is his most celebrated book in medicine, presents a summary of all the medical knowledge of his time. Ibn-Sina wrote a complete section about kidney calculi in his book. Totally, 65 herbal, 8 animal, and 4 mineral medicines are mentioned in the Canon of Medicine as beneficial drugs for destructing, expelling, and preventing kidney calculi. Ibn-Sina introduced very advanced drug designing based on drug delivery, targeting the organ, deposition in the site of action, pain control, wound healing, clearance after action, and supporting the organ. Using Ibn-Sina’s ideas help scientists to choose better drugs with a historical background to reduce the cost of therapies and research projects.